1994
DOI: 10.1002/ijc.2910560604
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of female breast cancer in relation to prevalence of risk factors in Denmark

Abstract: The extent to which changes in prevalence of risk determinants for female breast cancer could explain the temporal variation in incidence was examined using incidence figures from Denmark for the years 1943-1989. Significant increases in incidence were observed for more recent time periods and birth cohorts. Using deviance statistics from Poisson regression measures of variability explained, only a small proportion of the increase in incidence could be accounted for by fertility rates, average age at menarche … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…J. Cancer, 70:159-163, 1997.r 1997 Wiley-Liss, Inc.Breast cancer is the most common neoplasm in women in developed countries, though its rates vary considerably across different populations (Harris et al, 1992;Ewertz and Duffy, 1994;Levi et al, 1994;Lipworth, 1995). A role of several hormonal factors in terms of relative risks has been consistently reported (Henderson, 1993;Kelsey et al, 1993;Lipworth, 1995), and although the strength of the associations for each risk factor or their combinations is not very elevated, their variation may well at least partly explain the national differences in breast cancer incidence and mortality (La Vecchia and Pampallona, 1986;Harris et al, 1992).…”
mentioning
confidence: 99%
“…J. Cancer, 70:159-163, 1997.r 1997 Wiley-Liss, Inc.Breast cancer is the most common neoplasm in women in developed countries, though its rates vary considerably across different populations (Harris et al, 1992;Ewertz and Duffy, 1994;Levi et al, 1994;Lipworth, 1995). A role of several hormonal factors in terms of relative risks has been consistently reported (Henderson, 1993;Kelsey et al, 1993;Lipworth, 1995), and although the strength of the associations for each risk factor or their combinations is not very elevated, their variation may well at least partly explain the national differences in breast cancer incidence and mortality (La Vecchia and Pampallona, 1986;Harris et al, 1992).…”
mentioning
confidence: 99%
“…Ewertz and Duffy 28 reported that the changes in the breast cancer incidence rates in Denmark for 1943-1989 could not be explained wholly by changes in fertility but that a considerable part may be explained by changes in dietary habits and alcohol consumption. They did not, however, use the most important reproductive predictor namely the percentage of nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we analyzed the trend in female breast cancer incidence in Miyagi Prefecture, Japan during 1959–1987, and indicated the importance of a period effect 5. At that time, although studies from the US and Nordic countries have reported significant cohort effects on breast cancer incidence,6, 7, 8 a cohort effect on incidence has been uncertain in Japan. We concluded that it might still take some time before the cohort effect emerges 5.…”
mentioning
confidence: 99%